Existence of radial solutions for nonlinear elliptic equations with gradient terms in annular domains. (October 2019) - Dong, Xu; Wei, Yuanhong
Abstract: This paper is concerned with the problem of elliptic equations in annular domains involving derivative terms. Using nonlinear analysis methods, some results regarding existence of solutions are established. More precisely, at least one radial solution is obtained basing on Schauder's fixed point theorem and contraction mapping theorem, respectively. Some iterative technique is also applied, which allows us to overcome difficulties that the nonlinearity is related to derivative terms.